2014
DOI: 10.3139/105.110217
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Properties of Pearlitic Steel during Cold Wire Drawing: A Residual Stress Perspective*

Abstract: The residual stress evolution during cold drawing of pearlitic steel wire was followed over a broad strain range by diffraction techniques. The present work discusses possible links between microstructural changes induced by severe deformation and their “footprints” left in the residual stresses on different – macro, micro and nano – scale levels. Energy dispersive synchrotron diffraction revealed a significant divergence in the grain microstress evolution among differently oriented ferrite grains in the high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Moreover, one can clearly observe a trend of the ferrite grain microstress saturation in the range of ε t = 0.6 -2.3. This finding fits with the present (growing tensile) total phase stress evolution and the assumed predominant role of macrostress in this regime [2,3]. Analogously to the reduction of axial internal stresses during loading of pearlitic steel [5], a competition between elastic and plastic anisotropy in the ferrite leads to the monotonous residual grain microstress evolutions.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Moreover, one can clearly observe a trend of the ferrite grain microstress saturation in the range of ε t = 0.6 -2.3. This finding fits with the present (growing tensile) total phase stress evolution and the assumed predominant role of macrostress in this regime [2,3]. Analogously to the reduction of axial internal stresses during loading of pearlitic steel [5], a competition between elastic and plastic anisotropy in the ferrite leads to the monotonous residual grain microstress evolutions.…”
Section: Resultssupporting
confidence: 86%
“…This can be attributed to inhomogeneous elastic and plastic deformation of cementite lamellae and ferrite matrix, respectively [2]. Recently, a microstructural analysis pointed to a dependence of the evolutions of the apparent interlamellar spacing and cementite lamellas thickness on the alignment of the lamellae with respect to the drawing direction [3]. It has been suggested that the cementite lamellae of pearlite undergo predominantly elastic deformation during the first passes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations